Technological Pedagogical Content Knowledge (TPACK) pada Guru SMP dan SMA di Jabodetabek - Pratami, Elisabeth Vania; Ajisuksmo, Clara R. P. (Fakultas Psikologi Universitas Sanata Dharma, 2024)
Technological advances are developing very rapidly and have become a part of human life in the 21st century. The digitalization era demands that educational institutions and the parties within them carry out educational transformation by changing the learning paradigm. This is done in response to changing times that require new skills in global society. 21st century learning emphasizes learning that is integrated with technology. Therefore, educators need skills in mastering three fundamental components, namely content, pedagogy, and technology, which can be understood through the Technological Pedagogical Content Knowledge (TPACK) framework. This study aims to determine the integration of technology by private middle and high school teachers in Jabodetabek in 21st century learning based on the TPACK component. A total of 138 participant data was obtained by self-report via electronic questionnaire using convenience sampling and analyzed using the descriptive statistical analysis method. The study results show that teachers have adequate knowledge regarding the integration of technology in the education sector because the majority of teachers' scores are in the high category. The Covid-19 pandemic has also increased the integration of technology in the learning process. In utilizing technology, most teachers use Google Classroom as a type of Learning Management System (LMS) that can increase learning efficiency.